Birth as an American rite of passage - Davis-Floyd, Robbie (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This classic book, first published in 1992 and again in 2003, has inspired three generations of childbearing people, birth activists and researchers, and birth practitioners-midwives, doulas, nurses, and obstetricians-to take a fresh look at the "standard procedures" that are routinely used to "manage" American childbirth. It was the first book to identify these non-evidence-based obstetric interventions as rituals that enact and transmit the core values of the American technocracy, thereby answering the pressing question of why these interventions continue to be performed despite all evidence to the contrary. This third edition brings together Davis-Floyd's insights into the intense ritualization of labor and birth and the technocratic, humanistic, and holistic models of birth with new data collected in recent years"--
Keywords: Childbirth -- Social aspects -- United States; Childbirth -- United States -- Psychological aspects; Rites and ceremonies -- United States; HEALTH & FITNESS / Pregnancy & Childbirth; SOCIAL SCIENCE / Anthropology / General